2019
DOI: 10.21067/jem.v15i1.3041
|View full text |Cite
|
Sign up to set email alerts
|

Dividend payout among Nigerian firms: Do female directors matters?

Abstract: This study explores how female director(s) affect the decision to pay dividend in the sub-Saharan Africa. The study specifically employs non-financial firms listed on the Nigerian Stock Exchange Market from 2009-2015 and logit regression as the technique for data analysis. The independent variable of interest in the study is female director. Consistent with the hypothesis, the study found strong association that firms with at least one female director on board are more likely to affect the payment of dividends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Control variables are widely used in correlational studies similar to this work (Idris, Ishak & Hassan, 2019;Gyapong & Afrifra, 2019;Shehu, 2015). They refer to variables that are not of primary interest to the study but are considered to be of importance due to the effect that they may have on the results.…”
Section: Control Variablesmentioning
confidence: 94%
“…Control variables are widely used in correlational studies similar to this work (Idris, Ishak & Hassan, 2019;Gyapong & Afrifra, 2019;Shehu, 2015). They refer to variables that are not of primary interest to the study but are considered to be of importance due to the effect that they may have on the results.…”
Section: Control Variablesmentioning
confidence: 94%
“…This study followed prior studies on the propensity to pay dividends (Al-Najjar & Kilincarslan, 2016; Arko, Abor, Adjasi & Amidu, 2014; Idris, Ishak & Hassan, 2019) to model the dependent variable. The dependent variable was a binary variable, which was coded as 1 if a company paid a dividend and 0 if otherwise during the period of study.…”
Section: Dependent Variablementioning
confidence: 99%
“…However, due to this, there are various divergent views about the role of board dynamism on dividend payout ratio of firms. For example, some scholars such Ul Ain, Yuan, Javaid, Zhao and Xiang [14], Dissanayake and Dissabandara [15], Almeida, Firmino and Coelho [16], Gyapong, Ahmed, Ntim and Nadeem [17], Adamu, Ishak and Hassan [18], Chen, Leung and Goergen [19], Byoun, Chang and Kim [20] are of the view that board dynamism have positive influence on dividend payout ratio, while Nwidobie [21], Suwaidana and Khalaf [22], Pucheta-Martínez and Bel-Oms [23], Okafor, Ugwuegbe, Ugochukwu and Ezeaku [24], Sindhu, Hashmi and Haq [25], Ibrahim and Shuaibu [26], Dandago, Farouk and Muhibudeen [27], Aydin and Cavdar [28] have contrary view that board dynamism have inverse relationship with dividend payout ratio. Therefore, it can be concluded that available literatures in this area are mixed and inconclusive.…”
Section: Introductionmentioning
confidence: 99%